The demand for populism. A psycho-cultural based analysis of the desire for non mainstream political representation - Mannarini, Terri; Rochira, Alessia; Ciavolino, Enrico; Russo, Federico; Salvatore, Sergio (Psychology Hub, 2020)
Inspired by Semiotic Cultural Psychology Theory, the study surveyed a representative Italian national sample (N=818) to test a culture-based model of populist voting. The model assumed that a set of socio-political orientations (i.e., support for democracy, civicness, egalitarianism, anti-elitism, confidence in institutions, and respect for diversity) would mediate the relationship between symbolic universes (i.e., generalized affect-laden sets of meanings) and mainstream vs. populist voting. The results supported the main hypotheses, revealing that populist voting was favoured by a combination of concern for democracy and distrust. As expected, symbolic universes affected socio-political orientations, while a structural variable such as socio-economic status proved to be irrelevant. Implications for the SCPT framework and for research on populism and voting behaviour are discussed.